Design of concrete structures - Nilson, Arthur H. (McGraw-Hill, 2009)
Design of Concrete Structures covers the behavior and design aspects of concrete and provides updated examples and homework problems. New material on slender columns, seismic design, anchorage using headed deformed bars, and reinforcing slabs for shear using headed studs has been added. The notation has been thouroughly updated to match changes in the ACI Code